Adequacy of legal protection for women against domestic violence: revisiting the current policies & laws in Malaysia - Che Soh @ Yusoff, Roslina; Mohd Zin, Najibah; Md Hashim, Noraini (2013)
Despite having sophisticated laws and policies regulating domestic violence, problems on either the husband or wife being battered are endless. Worst still, domestic violence against women has become one of the major problems across the world. It cuts across lines of races, religion, income and classes of people. It is also deeply embedded in all cultures, so much so that millions of women consider it as a way of life. In Malaysia, the issue of domestic violence on women is one of the main agendas of the government’s policy on women. Under this policy, various programmes and laws have been introduced to regulate and control the problem of domestic violence against women. This paper seeks to discuss the Malaysian policy on the protection of women against domestic violence and the current applicable laws and remedies and to present to what degree these laws are adequate in controlling the problem of domestic violence on women in Malaysia.